The impact of work-based research projects at postgraduate level. Issue 1 (6th October 2015) - Costley, Carol; Abukari, Abdulai
Abstract : Purpose: The purpose of this paper is to examine the impact of work-based research projects at postgraduate level. The focus of this paper is to measure the impact of masters- and doctoral-level work-based projects which was the specific contribution of one group of researchers to the Nixon et al. 's (2008) study. Design/methodology/approach: This paper is based on data generated as part of a wider study that examines the impact of work-based learning projects across undergraduate through to doctoral level from the perspective of employers and from the employees perspective. The research study is based on a sample of alumni who had graduated from work-based masters and professional doctorate programmes and their corresponding employers in a UK higher education institution. Findings: At masters and doctorate level the work-based project can often make an impact on the work context and also have a developmental effect on the employee who becomes a practitioner-researcher to undertake the project. Originality/value: This paper finds that work-based projects are often an investment that companies make that have the propensity to yield tangible business success as well as providing an incentive for key staff to remain in the company and achieve university recognition.